What makes a journal international? A case study using conservation biology journals - Calver, M.; Wardell-Johnson, Grant; Bradley, S.; Taplin, Ross (Akademiai Kiado Rt., 2010)
The qualitative label ‘international journal’ is used widely, including in national research quality assessments. We determined the practicability of analysing internationality quantitatively using 39 conservation biology journals, providing a single numeric index (IIJ) based on 10 variables covering the countries represented in the journals’ editorial boards, authors and authors citing the journals’ papers. A numerical taxonomic analysis refined the interpretation, revealing six categories of journals reflecting distinct international emphases not apparent from simple inspection of the IIJs alone. Categories correlated significantly with journals’ citation impact (measured by the Hirsch index), with their rankings under the Australian Commonwealth’s ‘Excellence in Research for Australia’ and with some countries of publication, but not with listing by ISI Web of Science. The assessments do not reflect on quality, but may aid editors planning distinctive journal profiles, or authors seeking appropriate outlets.